Effect of sowing date and planting method on yield and components yield of three varieties of quinoa (Chenopodium quinoa Willd) - Golabi, Mehrnoosh; Lak, Shahram; Gilani, Abdolali; Alavi Fazel, Mojtaba; Egdernezhad, Aslan (Italian Journal of Agronomy, 2024)
The most important parameter for the adaptability a crop to different climates is the planting date which has the greatest influence on the phonological characteristics of the plant. Therefore, this study was conducted to determine whether it is possible to plant different varieties of quinoa at different planting dates in hot and dry climates. The experiment was conducted as a split-plot experiment based on a randomized complete block design with four replications in two crop years, 2018-2019 and 2019-2020. The planting date was considered as the main plot at four levels (October 21, October 31, November 10 and November 20), the planting method (transplanting and seed sowing) as the sub-plot and the quinoa varieties (Gizal, Q26 and Titicaca) as the sub-sub-plot. The results showed that delays in planting date reduced leaf area index (LAI), plant height, grain yield components, grain yield and biological yield of quinoa. The highest values for these traits were recorded for the first sowing date of October 21, and early/late transplanting was inferior and superior to direct seed sowing, respectively. Among the varieties studied, Q26 variety was superior to the other two varieties in terms of growth, yield components and grain yield. The highest grain yield (3190 kg/ha) was recorded for Q26 under direct sowing on October 21 and the lowest (733 and 721 kg/ha) for Titicaca under direct sowing on November 20 and 30, respectively. Overall, early autumn sowing was suitable for growing different quinoa varieties in Khuzestan province due to longer growing period and avoiding the heat stress at the end of the growing period. Transplanting did not have much advantage over early seed sowing, but was better than delayed seed sowing.